Kode etik dalam eksistensi profesi pustakawan - Hidayah, Nurul (Maliki Interdisciplinary Journal, 2024)
This study aims to explain the code of ethics of librarians in carrying out their duties as librarians. Some guidelines must be understood and implemented when providing services to libraries or users of the library. This study uses the method of libraries by conducting a literary analysis of journal articles and books that have the same topic of discussion.